1997
DOI: 10.1007/bf02404759
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-enhanced movement of arsenic out of lead arsenate-contaminated topsoil and through uncontaminated subsoil

Abstract: Abstract. Past use of lead arsenate insecticides has resulted in elevated concentrations of lead (Pb) and arsenic (As) in topsoils of many existing and former deciduous tree fruit orchard sites throughout the world. Application of phosphate (PO4)-containing fertilizers to these soils can increase soil As solubility, phytoavailability and downward mobility. A laboratory soil column experiment was conducted to determine if As released by phosphate additions to a topsoil artificially contaminated with lead arsena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(79 citation statements)
references
References 19 publications
(5 reference statements)
5
73
0
1
Order By: Relevance
“…The As concentration in basal fertilizers (NPK) is low (0.03-5.2 mg/kg), suggesting the increase of As in grain is not due to the application of basal fertilizers. The most plausible explanations are (a) the competition between phosphate (PO 4 2− ) originating from the NPK fertilizers and arsenate in the soil may release As into pore water (Peryea and Kammereck 1997;Peryea 1998;Wang et al 2002), leading to increased As bioavailability and higher uptake of As by the plants, or (b) the NPK fertilizers may stimulate microbial activity, which reduces Fe or As in soil, releasing the As adsorbed on the Fe minerals and causing increased availability of As. The addition of rice straw into the soil (NPK+RS) significantly increased the As concentration in rice grain by 12.2 and 26.4 % compared with the NPK and control treatments, respectively.…”
Section: Discussion Effect Of Si On As Concentration In Rice Grainmentioning
confidence: 99%
“…The As concentration in basal fertilizers (NPK) is low (0.03-5.2 mg/kg), suggesting the increase of As in grain is not due to the application of basal fertilizers. The most plausible explanations are (a) the competition between phosphate (PO 4 2− ) originating from the NPK fertilizers and arsenate in the soil may release As into pore water (Peryea and Kammereck 1997;Peryea 1998;Wang et al 2002), leading to increased As bioavailability and higher uptake of As by the plants, or (b) the NPK fertilizers may stimulate microbial activity, which reduces Fe or As in soil, releasing the As adsorbed on the Fe minerals and causing increased availability of As. The addition of rice straw into the soil (NPK+RS) significantly increased the As concentration in rice grain by 12.2 and 26.4 % compared with the NPK and control treatments, respectively.…”
Section: Discussion Effect Of Si On As Concentration In Rice Grainmentioning
confidence: 99%
“…Arsenic is slightly more soluble and will move through the soil profile (Focus, 2006). Arsenic mobility is enhanced by addition of phosphorus (Peryea & Kammereck, 1997). Arsenic is more mobile compared to lead regardless of the soil type and texture (Eflving et al, 1994).…”
Section: Occurrence Of Lead Arsenate In the Environmentmentioning
confidence: 99%
“…Remediation of lead arsenate contaminated soils, however, is more challenging because of (1) the vast amount of lead arsenate contaminated soil throughout the world (Peryea & Kammereck 1997), and (2) some of the common in situ remediation methods that have been proven effective for the remediation of lead contaminated soils result in the release of arsenic from lead arsenate contaminated soil, thereby creating a new environmental problem (Codling, 2007;Peryea 1991b). Phosphate, for example, has been shown to be very effective in sequestering lead in contaminated soils (Chaney & Ryan 1994;Ruby et al, 1994), but this remediation method is not suited for lead arsenate contaminated soil; because arsenate and phosphate exhibit similar physicochemical behavior in soil and compete directly for sorption sites on soil particles, the use of phosphate on a lead arsenate contaminated soil will promote arsenic release from the soil into the soil solution phase, threatening the ground water (Dupanport & Peryea 1991b;Eflving et al, 1994;Peryea & Kammereck 1997;Peryea, 1991). Increasing the number of adsorption sites via the addition of high oxide minerals such as iron and manganese might allow for the resorption of arsenate after its release caused by phosphate competition during lead sequestration.…”
Section: In Situ Remediation Of Lead and Arsenicmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of this additional As to human and/or environmental health in southeastern Virginia is currently unknown. However, application of phosphorous-rich fertilizers to these soils, many of which are overlain by lawns, could potentially lead to the mobilization of the added As in Norfolk soils (e.g., Peryea and Kammereck 1997). Furthermore, a recent study demonstrated that children playing in playgrounds with chromated copper arsenate treated wooden playground structures or with sand that has come in contact with such structures, acquire more soluble As on their hands compared to children not exposed to such structures or the associated sand (Kwon et al 2004).…”
Section: Arsenic (Mg/kg)mentioning
confidence: 99%